Toxocariasis in children: seroprevalence after 15 years in a major city in Brazil - Lima, Viviane dos Santos Vaccaro; Ferreira, Isabella Braghin; Rapchan, Gabriela Geraldi da Silva; Lescano, Susana Zevallos; Rodrigues e Fonseca, Gabriela; Giuffrida, Rogerio; Kmetiuk, Louise Bach; Biondo, Alexander Welker; Santarém, Vamilton Alvares (Frontiers in Pediatrics, 2025)
IntroductionChildren have a potentially greater exposure to Toxocara spp. infection via egg ingestion due to playground soil contact. Understanding the associated risk factors may help to prevent infection in children; however, there were no studies that monitored urban seropositivity over time. Therefore, we aimed to assess Toxocara seroprevalence and the associated risk factors in children who regularly accessed the Public Health System in a major city area in southeastern Brazil over a period of 15 years (2008–2023).MethodsA cross-sectional study was designed in 2023–2024 to screen for anti-Toxocara antibodies in children through an enzyme-linked immunosorbent assay alongside an epidemiological questionnaire to assess health status and living conditions. Univariate and multivariate logistic regression analyses were used to investigate the factors associated with seropositivity in children.ResultsIn total, 30/260 [11.5%; 95% confidence interval (CI): 8.2%–16.0%] children were found to be seropositive for Toxocara spp. Boys were at a higher exposure risk [odds ratio (OR): 4.4] to toxocariasis than girls. Having a mother with a graduate degree (OR: 0.21; p = 0.016), receiving drinkable water supply (OR: 0.29; p = 0.017), and having hygienic habits of washing hands before meals (OR: 0.32; p = 0.033) were protective factors. The findings presented no significant difference (p = 0.879) when compared to those of a previous 2008 serosurvey, with 28/252 (11.1%; 95% CI: 7.8%–15.6%) seropositive children.DiscussionToxocara seroprevalence in children living in an urban area did not significantly change over the 15 years since the previous serosurvey was conducted. As no mitigatory actions were carried out between the surveys, we speculate that environmental contamination and child exposure to Toxocara spp. remained steady. However, future surveys should include soil detection of Toxocara spp. to fully establish the role of environmental contamination over time. In conclusion, although toxocariasis in children may not increase over time, such seroprevalence may not decrease either, persisting (even in low levels) for long periods.